Martin Dreher, Athen und Sparta, C.H. Beck Verlag, Múnich, 2001, 214 pp. y cinco mapas, ISBN 3-406-48208-2 (Minerva, 2019)
Review: Martin Dreher, Athen und Sparta, C.H. Beck Verlag, Múnich, 2001, 214 pp. y cinco mapas, ISBN 3-406-48208-2